(3cTa GdCSQGQ Yf hVY MQha GdZHGQs - (3CHh GdMSf Ydj Hf eMeO GdbQTi GdTgjQ HGdbdUGhis; (3GdbdUGOj , CHh GdMSf,J (B891 (3g` s
(3ChdgG (B:s
(3GdMeO ddg SQjY GdMSGH , eSHd GdfYeGA haGJM GdCHhGH CeG HYO , agPg fHPI cGajI TGajI , hYf LGfHi GdENdGd hGdEedGd eJLGajI , EbJWaJgG ef cJGHi GdeSei H (B" (3cTa GdLdHGH Yf Yde GdMSGH (B" (3, dJchf ZfjI dHYV GdWdGH s
(3BNQgG (B:s
(3BNQ GdehLhO efgG (B: (3aUd (B: (3hEPG cGf ai CMO GdeLehYjf Ch ajgeG eYkG ESJKfGA aGJQcg Ydi MGdg , hGLeY GdLfS Edi eKdg , hZjQ GdLfS HMQa GdYWa , hebGd ef Pdc (B: (3ZPG bHd dc GLeY s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3MhGa HYV GdChQGb eJbWaI CJJ Ydi HYV GdSWhQ s
(3fSNI eUMMI ebGHdI s
(3JHUQI GdYfhGf (B:s
Keywords: (3GdMQha h GdChaGbs